Rancang Bangun Aplikasi Angkotkita Menggunakan Location Based Service Dengan Metode Haversine Berbasis Android - Imamsyah, Rasyid Noor; Sari, Nova Noor Kamala; Lestari, Ariesta (Universitas Palangka Raya, 2023)
One of the problems that are often encountered by city transport passengers is the uncertainty that there will be city transportation that will pass through the passenger's location and uncertainty regarding the number of passengers in the city transportation. Meanwhile, the problem for city transportation drivers is the uncertainty of the location of passengers who will order city transportation and the location of passengers who are scattered, making the driver have to stop several times even though the location between passengers and others is not too far away. This study aims to create a city transportation service application using a location based service (LBS) with the haversine method. The research methodology used is extreme programming which has four stages, namely planning, design, coding, and testing. The results of the study are the AngkotKita Application for passengers and the AngkotKita Application for drivers. Applications for passengers provide information about the route from the passenger's starting point to the nearest bus stop, information on city transportation that will pass the bus stop, detailed information on passenger orders both ongoing and completed, and promo information and news. Applications for drivers provide information in the form of being able to see bus stops containing passengers, user profile information, driver's incoming and outgoing QR Code information, information on ongoing and completed orders.